2009
DOI: 10.1074/jbc.m809304200
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Interactions Between the Src Homology 3 Guanylate Kinase Domains of Discs Large Regulate Its Function in Asymmetric Cell Division

Abstract: Membrane-associated guanylate kinases (MAGUKs) regulate the formation and function of molecular assemblies at specialized regions of the membrane. Allosteric regulation of an intramolecular interaction between the Src homology 3 (SH3) and guanylate kinase (GK) domains of MAGUKs is thought to play a central role in regulating MAGUK function. Here we show that a mutant of the Drosophila MAGUK Discs large (Dlg), dlg sw , encodes a form of Dlg that disrupts the intramolecular association while leaving the SH3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 61 publications
2
29
0
1
Order By: Relevance
“…Deletion of or replacement of the PDZ3/SH3-linker with flexible residues diminishes the GuK-mediated binding to GuK-Holder (5). Additionally, binding of a target peptide to PDZ3 weakens the GuK-Holder binding ability of the SH3-GuK module, implying a conformational coupled allosteric regulation between PDZ3 and SH3-GuK (6). In another example, the interaction of the GuK domain of mammalian PSD-93/ DLG2 to MAP1a is also allosterically regulated by its PDZ3, albeit in this case, binding of the PDZ ligands releases its inhibition of the GuK/MAP1a interaction (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of or replacement of the PDZ3/SH3-linker with flexible residues diminishes the GuK-mediated binding to GuK-Holder (5). Additionally, binding of a target peptide to PDZ3 weakens the GuK-Holder binding ability of the SH3-GuK module, implying a conformational coupled allosteric regulation between PDZ3 and SH3-GuK (6). In another example, the interaction of the GuK domain of mammalian PSD-93/ DLG2 to MAP1a is also allosterically regulated by its PDZ3, albeit in this case, binding of the PDZ ligands releases its inhibition of the GuK/MAP1a interaction (22).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Recent studies have demonstrated that functional interaction between Dlg SH3-GuK tandem and its partner GuKHolder is dependent on the presence of the upstream PDZ domain of Dlg and that this interaction is further regulated by the PDZ domain binding peptide (5,6). Considering the highly conserved domain organization feature of MAGUKs throughout evolution, we hypothesized that the signature PDZ-SH3-GuK tandem of MAGUKs may form a structural supramodule with three domains interacting with each other to assemble into an integral structural unit, which has functions distinct from those of the isolated domains or the simple sum of the individual domains.…”
mentioning
confidence: 99%
“…In the fly, SH3-Hook mutants or mutations that otherwise disrupt SH3-GUK binding phenocopy DLG null mutants (50,51); thus, this region is critical for the function of this scaffolding protein. The Hook domain of DLG1 cooperates with the SH3 domain to bind the GUK intramolecularly and regulate the accessibility of this domain to binding partners (52).…”
Section: Discussionmentioning
confidence: 99%
“…1a,b). A mutant of Dlg, dlg sw , bearing a COOHterminal truncation following the GUK domain, comparable to a 13-aa truncation of PSD-95 containing the bF strand, disrupted the intramolecular SH3-GUK interaction both in Dlg and PSD-95 while leaving the SH3 and GUK domains intact 12 . The bF truncation of CARMA1 corresponding to the dlg sw mutation disrupted the intermolecular SH3-GUK interaction of CARMA1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All MAGUK proteins comprise one to three PDZ domains, an SH3 domain and a GUK domain that lacks catalytic activities but which acts as a protein interaction domain. Previous studies have suggested that organization of the protein complex by MAGUKs occurs through allosteric regulation of intra-and intermolecular interactions via the SH3 and GUK domains [6][7][8][9][10][11][12] . The importance of the SH3-GUK domain interaction for MAGUK function was demonstrated by genetic studies in invertebrates that identified numerous loss-of-function mutations in the SH3 and GUK domains of disc large (dlg) in Drosophila 13 and lin-2 in Caenorhabditis elegans 14 , all of which could disrupt SH3-GUK interactions 6 .…”
mentioning
confidence: 99%